Probiotic and Antifungal Attributes of Levilactobacillus brevis MYSN105, Isolated From an Indian Traditional Fermented Food Pozha - Somashekaraiah, Rakesh; Mottawea, Walid; Gunduraj, Adithi; Joshi, Udit; Hammami, Riadh; Sreenivasa, M. Y. (Frontiers in Microbiology, 2021)
The use of probiotics and antifungal capabilities of the lactic acid bacteria (LAB) isolated from different niches is a strategy to prepare functional cultures and bio-preservatives for food/feed industries. In the present study, LAB strains isolated from an Indian traditional fermented food- Pozha, were evaluated for their probiotic properties and biocontrol potential. A total of 20 LAB isolates were selected from Pozha samples collected aseptically and screened for their antagonistic activity against Fusarium verticillioides. Among the bioactive isolates, Lacticaseibacillus brevis MYSN105 showed the highest antifungal activity in vitro, causing some morphological alterations such as damaged mycelia and deformed conidia. Cell-free supernatant (CFS) from L. brevis MYSN105 at 16% concentration effectively reduced the mycelial biomass to 0.369 g compared to 1.938 g in control. Likewise, the conidial germination was inhibited to 20.12%, and the seed treatment using CFS induced a reduction of spore count to 4.1 × 106 spores/ml compared to 1.1 × 109 spores/ml for untreated seeds. The ITS copy number of F. verticillioides decreased to 5.73 × 107 and 9.026× 107 by L. brevis MYSN105 and CFS treatment, respectively, compared to 8.94 × 1010 in control. The L. brevis MYSN105 showed high tolerance to in-vitro gastrointestinal conditions and exhibited high adhesive abilities to intestinal epithelial cell lines. The comparative genome analysis demonstrated specific secondary metabolite region coding for bacteriocin and T3PKS (Type III polyketide synthase) possibly related to survival and antimicrobial activity in the gut environment. Our results suggest that L. brevis MYSN105 has promising probiotic features and could be potentially used for developing biological control formulations to minimize F. verticillioides contamination and improve food safety measures.